Modeling and Analysis of The Savonius Type L Wind Turbine with Variations in Geometry and Number of Blades on Airflow Using CFD (Computational Fluid Dynamics) Method - Komarudin Komarudin; Arif Khasani (Greenation Research & Yayasan Global Resarch National, 2025)
The use of fossil energy has a negative impact on the preservation nature, wind turbines are one form of renewable energy utilization solutions that are environmentally friendly. This study was conducted to determine the performance of the L-type Savonius vertical axis wind turbine modified with variations in geometry and number of blades against airflow. Based on the simulation results using Ansys 2023 student version, it is known that the smaller the angle of attack of the blade, the greater the potential power , while the increase in the number of blades makes the potential power decrease. Turbines with the number of blades 3 with an angular geometry of 30° have the most optimum performance, namely with a maximum airflow velocity at the tip of the turbine blade of 11.2 m/s, the resulting torque of 2345 Nm with an optimum angular velocity of 46.914 rad/s resulting in a potential power of 110.014 Watt.